Abuse of Power as The Cause of Language Impoliteness in The Text Drama Majlisu Al-Adli by Taufiq Al-Hakim - Zumrotul Imanda Wachid Hakim (Universitas Ahmad Dahlan, 2025)
This study aims to identify the forms and analyze the causes of linguistic impoliteness in Taufiq al-Hakim’s drama Majlisu al-‘Adli by applying Jonathan Culpeper’s theory of linguistic impoliteness. It addresses the lack of research on impoliteness in Arabic drama texts, particularly regarding its causes, and demonstrates how linguistic impoliteness reflects power abuse in Arabic literary works. The study employs a qualitative descriptive method, collecting data through a reading and note-taking technique on dialogues that contain impolite expressions. The findings show that The Judge’s impoliteness manifests in face attacks, intentional strategies, hearer perceptions, and communicative tactics such as sarcasm and legal manipulation. The primary cause of this impoliteness lies in the abuse of power, as The Judge exploits his authority to defend certain parties and dismiss justice. This study also suggests that further research is needed on the relationship between linguistic impoliteness and humor in dramatic texts as a form of social critique.